Answer:
Jorge, do your own work
Answer:
Step-by-step explanation:
On average Christopher scores 2 goals per game
If the play is hard his goal total varies by 1 from the average
If the play is easy his goal total varies by 1 from the average
That is Christopher can score 1 goal more or 1 goal less depending upon the opponent team
He score maximum goals of 3 in a game or 1 in a game
The equation |x-2| = 1
When x = 3
|3-2| = 1
|1| = 1 True
When x = 1
|1-2| = 1
|-1| = 1
1 = 1 True
4. A square court for playing the game four square has an area of 256 ft?. How long is one
side of the court?
Solve the inequality -5(3x+4)<6-3x
Answer:
x>-13/6
Step-by-step explanation:
First you multiply inside the bracket by -5 on left side. You get
-15x-20<6-3x
Then you place the like terms on same sides for which you add 3x to both side to get rid of 3x from right side and you add 20 to both sides to get ride of 20 from left side
-15x+3x<20+6
then you solve for x
-12x<26
x<-26/12
x> -13/6 (the inequality sign changes due to multiplication by a negative number)
Draw a model. Then, write the numerical expressions.
a. The difference between 8 forty-sevens and 7 forty-sevens
b. 6 times the sum of 12 and 8
Answer with Step-by-step explanation:
a. The difference between 8 forty-sevens and 7 forty-sevens
Let ⊕ repesents forty- sevens.
So, Model can be represented by
8⊕ - 7⊕
=⊕⊕⊕⊕⊕⊕⊕⊕-⊕⊕⊕⊕⊕⊕⊕
=⊕
Mathematically,
let x represents forty-sevens.
So, it becomes
[tex]8x-7x=x[/tex]
b. 6 times the sum of 12 and 8.
Mathematically, it is expressed as
[tex]6\times (12+8)\\\\=6\times 20\\\\=120[/tex]
Let 12 be written as 4×3
and 8 be written as 4×2
Let ⊕ represents 4 i.e. fours.
so, there are sum of 2 fours and 3 fours.
So, it becomes,
6×(⊕⊕+⊕⊕⊕)
=6×(⊕⊕⊕⊕⊕)
=⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕
=4×30
=120
Answer:
thanks
Step-by-step explanation:
Gustavo wants to buy more than two sandwiches at the city fair. There are three sandwich stands, and each is offering a different deal.
Benny's Sandwiches 4 sandwiches for $5.00
ABC Sandwiches, Inc. 4 sandwiches for $6.00
Sandwich Hut 1 sandwich for $2.00 *Buy 1, get 1 Free*
Answer:
sandwich hut is the best deal (what's the question????)
Step-by-step explanation:
because sandwich hut is buy one get one free, one sandwich costs $1.00 ($2 divided by 2 sandwiches)
Benny's costs $1.25 per sandwich ($5 divided by 4 sandwiches)
ABC costs $1.50 per sandwich ($6 divided by 4 sandwiches)
Answer:
Sandwich hut is the best deal.
Step-by-step explanation:
Find the unit rate of each stand, and you find which one is the best deal.
Giving 15 points help
Image:
Answer: To find out the unlabeled one on the inside subtract 180- 123, then you Get 57. Now do 180 = 57 + x +
92. Add up the whole numbers to get 180 = 149 + x now subtract 149 from 180, to get 31 and it equals x TADA
Step-by-step explanation:
M
9. If LK = MK, LK = 7x-10, KN = x + 3, MN = 9x - 11. and KJ = 28, find L.
LK: 7-10 kn +3 INOX
LJ = LK + KJ
LJ= 7x 28
LJ = 78+ 38
The exact value of [tex]\( L \) is \(-\frac{44}{3}\).[/tex]
To find [tex]\( x \)[/tex], we need to use the fact that [tex]\( LK = MK \)[/tex] and apply the given values and equations.
1. Set up the equation for [tex]\( LK \)[/tex] and [tex]\( MK \):[/tex]
Since [tex]\( LK = MK \),[/tex] we can write:[tex]\[LK = MK\][/tex]Given:
[tex]\[LK = 7x - 10\][/tex][tex]\[MK = KN + MN\][/tex]2. Substitute the given expressions:
[tex]\[MK = KN + MN\][/tex][tex]\[MK = (x + 3) + (9x - 11)\][/tex][tex]\[MK = x + 3 + 9x - 11\][/tex][tex]\[MK = 10x - 8\][/tex]3. Set up the equation [tex]\( LK = MK \)[/tex]
[tex]\[7x - 10 = 10x - 8\][/tex]4. Solve for [tex]\( x \):[/tex]
[tex]\[7x - 10 = 10x - 8\][/tex][tex]\[-10 + 8 = 10x - 7x\][/tex][tex]\[-2 = 3x\][/tex][tex]\[x = -\frac{2}{3}\][/tex]5. Find [tex]\( L \):[/tex]
With [tex]\( x = -\frac{2}{3} \), substitute \( x \) into the expression for \( LK \):[/tex][tex]\[LK = 7x - 10\][/tex][tex]\[LK = 7 \left(-\frac{2}{3}\right) - 10\][/tex][tex]\[LK = -\frac{14}{3} - 10\][/tex]Convert 10 to a fraction:
[tex]\[LK = -\frac{14}{3} - \frac{30}{3}\][/tex][tex]\[LK = -\frac{44}{3}\][/tex]Thus, [tex]\( L \)[/tex] would be [tex]\(-\frac{44}{3}\)[/tex], assuming [tex]\( L \)[/tex] represents the value of [tex]\( LK \).[/tex]
The complete question is:
If LK = MK, LK = 7x-10, KN = x + 3, MN = 9x - 11. and KJ = 28, find L.
through(-3,0)and (0,3)
Answer:
Step-by-step explanation:
the equation line passes through(-3,0)and (0,3) is : y=ax+b
a is the slope a = (3-0)/(0+3) = 1
so : y= x +b calculate b line passes through(-3,0)and (0,3)
x=0 y=3 : 3 = 0+b so b= 3
this equation is : y= x+3
explain how you would find how many 1 1/2 cup servings there are in a pot that contains 22 1/2 cups of soup.
Step-by-step explanation:
multiply the 1 1/2 by 2 to get 3.
find the closest number that is divisible by 3
3*7 is 21.
We now have to multiply 7 by 2 since we did that to our mixed number to get a whole number.
There is still a 1 1/2 left over. Simply add 1 to 14.
Answer:
15 servings
Step-by-step explanation:
Given,
Total number of cups = [tex]22\frac{1}{2}[/tex]
The number of cups required for each serving = [tex]1\frac{1}{2}[/tex]
Thus,
[tex]\text{The number of servings}=\frac{\text{Total cups}}{\text{cups required for each serving}}[/tex]
[tex]=\frac{22\frac{1}{2}}{1\frac{1}{2}}[/tex]
[tex]=\frac{\frac{45}{2}}{\frac{3}{2}}[/tex]
[tex]=\frac{45}{3}[/tex]
= 15
Lucy earns money babysitting. Her earnings and hours worked represent a direct variation. She worked for 4 hours and earned $25.
Determine the constant of proportionality for dollars earned per hour worked
Determine the constant of proportionality for hours worked per dollar earned.
Final answer:
The constant of proportionality for dollars earned per hour worked is 6.25, and the constant of proportionality for hours worked per dollar earned is 0.16.
Explanation:
To find the constant of proportionality for dollars earned per hour worked, we can use the formula y = kx, where y is the amount earned and x is the number of hours worked. Given that Lucy earned $25 for 4 hours of work, we can substitute these values into the equation:
25 = k * 4
Solving for k, we divide 25 by 4:
k = 25 / 4 = 6.25
Therefore, the constant of proportionality for dollars earned per hour worked is 6.25.
To find the constant of proportionality for hours worked per dollar earned, we can rearrange the equation to x = my, where x is the number of hours worked and y is the amount earned. Substituting the values, we get:
4 = m * 25
Solving for m, we divide 4 by 25:
m = 4 / 25 = 0.16
Therefore, the constant of proportionality for hours worked per dollar earned is 0.16.
Simplify (3x2 − 2) + (5x2 + 5x − 1).
Answer: 9
The steps are in the picture
Answer:
8x² + 5x - 3
Step-by-step explanation:
Given
(3x² - 2) + (5x² + 5x - 1)
Since both parenthesis are distributed by 1 just remove them, that is
3x² - 2 + 5x² + 5x - 1 ← collect like terms
= (3x² + 5x²) + 5x + (- 2 - 1)
= 8x² + 5x - 3
Homeowners are building a square closet in a rectangular room that is 24 feet long and 18 feet wide. They want the remaining floor area to be at least 400 square feet. Because they don’t want to cut any of the 1 foot by 1 foot square floor tiles, the side length of the closet floor should be a whole number of feet. Make a table showing possible side lengths of the closet floor and the remaining area for each side length.
Answer: i can't speak english
Step-by-step explanation:
Which statement is true? A. 13/14 > 25/28 B. 21/45 < 4/9 C. 5/6 > 11/12 D. 4/5 < 8/25
Rewrite the fractions with common denominators and then answer:
A:
13/14 > 25/28
26/28 > 25/28
This is True
B) 21/45 < 20/45 False
C) 10/12 > 11/12
False
D) 20/25 < 8/25
False
The true statement is A.
Dr. Mann mixed 10.357 g of chemical a 12.062 g of chemical B and 7.506 g of chemical see to make five doses of medicine
Answer:
Part a) The estimate amount of medicine is 30.0 grams
Part b) The actual amount of medicine is 29.925 g. The difference between the estimate and the actual amount, is 0.075 g
Part c) 5.985 grams
Part d) 6 grams
Step-by-step explanation:
The complete question is
Dr. Mann mixed 10.357 g of chemical A, 12.062 g of chemical B, and 7.506 g of chemical C to make 5 doses of medicine.
a. About how much medicine did he make in grams? Estimate the amount of each chemical by rounding to the nearest tenth of a gram before finding the sum. Show all your thinking.
b. Find the actual amount of medicine mixed by Dr. Mann. What is the difference between your estimate and the actual amount?
c. How many grams are in one dose of medicine? Explain your strategy for solving this problem.
d. Round the weight of one dose to the nearest gram
Part a) round to the nearest tenth of a gram first
Chemical A
10.357 g -----> 10.4 g
Chemical B
12.062 g -----> 12.1 g
Chemical C
7.506 g -----> 7.5 g
To find out the estimate amount of medicine sum the three values
10.4+12.1+7.1=30.0 g
therefore
The estimate amount of medicine is 30.0 grams
Part b)
The actual amount of medicine is
10.357+12.052+7.506=29.925 g
To find out the difference between your estimate and the actual amount, subtract the actual amount from the estimate
30.0-29.925=0.075 g
Part c) To find out how many grams are in one dose of medicine, divide the actual amount of medicine by five
29.925 g/5=5.985 g
Part d) Round the weight of one dose to the nearest gram
we have
5.985 g ------> 6 g
Rosa has 412 punds of pizza dough. She uses 34
of a pound for one pizza. How many pizzas could be made from Rosa's dough?
(2x - 3) + [4x(3x + 2)] what is the answer
Answer:
22x-3
Step-by-step explanation:
(2x-3)+[4x(3x+2)]
(2x-3)+12x+8x
2x-3+20x
12x^2
I need help with number 5
Answer:
-14 *F
Step-by-step explanation:
-3 minus 11 is -14
hope this helps
Hey!
-------------------------------------------------
[tex]\large\boxed{A) -14~degrees~fahrenheit}[/tex]
-------------------------------------------------
Steps To Solve:
~Create an equation
-3 - 11
~Subtract
-14
-------------------------------------------------
Hope This Helped! Good Luck!
a has a coordinate (-2,4). B has a coordinate (9,11). find the coordinate of point p has a p that partion AB into a ratio 3:4
Answer:
see explanation
Step-by-step explanation:
Using the Section formula, then
[tex]x_{P}[/tex] = [tex]\frac{3(9)+4(-2)}{3+4}[/tex] = [tex]\frac{27-8}{7}[/tex] = [tex]\frac{19}{7}[/tex]
and
[tex]y_{P}[/tex] = [tex]\frac{3(11)+4(4)}{3+4}[/tex] = [tex]\frac{33+16}{7}[/tex] = [tex]\frac{49}{7}[/tex] = 7
Hence
P = ( [tex]\frac{19}{7}[/tex], 7 )
Complete each of the statements.
Answer:
Complete each of the statements below.
When work is done on a system by its surroundings, the sign of w is [ Select ] ["positive", "negative"] .
When work is done by a system on its surroundings, the sign of w is [ Select ] ["negative", "positive"] .
When q has a negative sign, we can say that heat is transferred [ Select ] ["from", "into"] the system [ Select ] ["from", "into"] its surroundings.
If ∆U for a system is 0 and w is negative, then q must be [ Select ] ["positive", "negative"] .
Step-by-step explanation:
1. Expression 1: [tex]\((3x^2 - 6x + 11) \cdot (10x^2 - 4x + 6)\)[/tex]:[tex]\[30x^4 - 72x^3 + 34x^2 - 44x + 66\][/tex]
2. Expression 2: [tex]\((-3x^2 - 5x + 3) \cdot (-10x^2 - 7x + c)\)[/tex]:[tex]\(30x^4 + 71x^3 + 5x^2 - 21x + 3c\).[/tex]
3. Expression 3: [tex]\((12x^2 + 6x - 5) \cdot (5x^2 + 8x - 12)\)[/tex]: [tex]\(60x^4 + 126x^3 + 53x^2 + 40x - 60\).[/tex]
the expressions step by step:
1. Expression 1: [tex]\((3x^2 - 6x + 11) \cdot (10x^2 - 4x + 6)\)[/tex]
To multiply these two expressions, we'll use the distributive property (also known as the FOIL method). Multiply each term in the first expression by each term in the second expression and then combine like terms.
- Multiply the first terms: [tex]\(3x^2 \cdot 10x^2 = 30x^4\)[/tex]
- Multiply the outer terms: [tex]\(3x^2 \cdot (-4x) = -12x^3\)[/tex]
- Multiply the inner terms: [tex]\((-6x) \cdot 10x^2 = -60x^3\)[/tex]
- Multiply the last terms: [tex]\((-6x) \cdot (-4x) = 24x^[/tex]2\)
Now add up all the results:
[tex]\[30x^4 - 12x^3 - 60x^3 + 24x^2 + 11 \cdot 10x^2 - 11 \cdot 4x + 11 \cdot 6\][/tex]
Combine like terms:
[tex]\[30x^4 - 72x^3 + 34x^2 - 44x + 66\][/tex]
So, the equivalent expression is:[tex]\(30x^4 - 72x^3 + 34x^2 - 44x + 66\)[/tex].
2. Expression 2: [tex]\((-3x^2 - 5x + 3) \cdot (-10x^2 - 7x + c)\)[/tex]
Follow the same steps as above to multiply the expressions:
- Multiply the first terms: [tex]\((-3x^2) \cdot (-10x^2) = 30x^4\)[/tex]
- Multiply the outer terms: [tex]\((-3x^2) \cdot (-7x) = 21x^3\)[/tex]
- Multiply the inner terms: [tex]\((-5x) \cdot (-10x^2) = 50x^3\)[/tex]
- Multiply the last terms: [tex]\((-5x) \cdot (-7x) = 35x^2\)[/tex]
Combine the results:
[tex]\[30x^4 + 21x^3 + 50x^3 + 35x^2 + 3 \cdot (-10x^2) + 3 \cdot (-7x) + 3c\][/tex]
Combine like terms:
[tex]\[30x^4 + 71x^3 + 35x^2 - 30x^2 - 21x + 3c\][/tex]
Simplify further:
[tex]\[30x^4 + 71x^3 + 5x^2 - 21x + 3c\][/tex]
So, the equivalent expression is: [tex]\(30x^4 + 71x^3 + 5x^2 - 21x + 3c\).[/tex]
3. Expression 3: [tex]\((12x^2 + 6x - 5) \cdot (5x^2 + 8x - 12)\)[/tex]
Apply the same process:
- Multiply the first terms:[tex]\(12x^2 \cdot 5x^2 = 60x^4\)[/tex]
- Multiply the outer terms: [tex]\(12x^2 \cdot 8x = 96x^3\)[/tex]
- Multiply the inner terms:[tex]\(6x \cdot 5x^2 = 30x^3\)[/tex]
- Multiply the last terms:[tex]\(6x \cdot 8x = 48x^2\)[/tex]
Combine the results:
[tex]\[60x^4 + 96x^3 + 30x^3 + 48x^2 + 5 \cdot 5x^2 + 5 \cdot 8x - 5 \cdot 12\][/tex]
Combine like terms:
[tex]\[60x^4 + 126x^3 + 53x^2 + 40x - 60\][/tex]
The equivalent expression is: [tex]\(60x^4 + 126x^3 + 53x^2 + 40x - 60\).[/tex]
7. Below are the points that Jesse scored in each game during the basketball season.
12, 15, 14, 12, 4, 8
Which of the following values would increase his mean number of points scored? Choose all that apply.
13
10
08
12
Answer:
13, 12, and 11. Im on connexus and when i submitted it said those are the correct answers. Hope it helps! :)
Step-by-step explanation:
What is the highest common factor of 24 and 76
Answer:
4 is the highest common factor
Answer:
The highest common factor is 4
Step-by-step explanation:
Factors of 24 are { 1,2,3,4,6,8,12.......}
And factors of 76 are{ 1,2,4,19......)
from the two factors,
common factor ( C. F ) ={1,2,4}
and from the common factors, the highest is 4
Therefore 4 is the highest common factor for 24 and 76.
Brice had $73 and then he earned d more dollars. Write an expression that shows how much money he has now.
Answer:
73+d
We don’t know what d equals so leave the variable, then just add the 73 he already had.
Step-by-step explanation:
a certain fish can swim 6 1/3 times faster than a person. if a person swims 5 7/8 miles per hour, how fast can the fish swim?
Answer: 37.2204mph
Step-by-step explanation: First, I converted 5 7/8 into 5.88 then I converted 6 1/3 into 6.33 and then multiplied the two then I got my answer.
Answer:
37 5/24 mph
Step-by-step explanation:
You need to multiply the numbers. First, convert them into fractions.
6 1/3 * 5 7/8 =
= (6 + 1/3) * (5 + 7/8)
= (6/1 + 1/3) * (5/1 + 7/8)
= (18/3 + 1/3) * (40/8 + 7/8)
= (19/3) * (47/8)
= 893/24
= 37 5/24
1 pound is now many grams
The answer is "453.592 grams." One pound does indeed equal 453.592 in grams.
Hope this helps.
Round the following numbers to the nearest 100. The numbers they have 324,558,256
Answer:
300, 600, 300.
Step-by-step explanation:
324: The tens digit is 2 so we do nothing to the hundreds digit so its 300.
558: The tens digit is 5 so we round up the 5 . So it is 600.
In a similar way 256 becomes 300.
Answer:
300, 600, 300
Step-by-step explanation:
When you round a number up by the nearest 100. The digit in the tens place must be equal to or more than 5.
For example: 250 is rounded up to 300, but 240 can not be rounded up to 300.
When you have a number like 240, it can only be rounded down to 200
324 is rounded down to 300 because the tens place digit is less than 5
558 is rounded up to 600 because the tens place digit is higher than 5.
256 is rounded up to 300 because the tens place digit is 5.
Draw segment EF so that is bisects RS. Mark their intersection appoint A
Step-by-step explanation:
EF is a segment so it's a line with the end points as E and F. Line RS bisects(cuts in half) line EF. Then where the two lines meet is where A is.
Hope this helped.
EF is a segment so it's a line with the end points as E and F. Line RS bisects(cuts in half) line EF. Then where the two lines meet is where A is.
To draw segment EF so that it bisects segment RS and mark their intersection point A, follow these steps:
Draw segment RS. This will be your starting line segment.
Find the midpoint of segment RS. To do this, measure the length of RS and mark the point that is exactly halfway between R and S. Let's call this point M.
Draw a straight line segment EF that passes through point M. This line segment will bisect segment RS.
Where segment EF intersects segment RS, mark the point of intersection as point A.
To know more about points:
https://brainly.com/question/22474261
#SPJ3
A horse began running due east and covered 25 km in 4.0 hr. What is the average
velocity of the horse?
Answer:
6.25 km an hour
please mark brainliest
Step-by-step explanation:
Answer:
Average velocity = 6.25 km/h
Step-by-step explanation:
Given : A horse began running due east and covered 25 km in 4.0 hr.
To find : What is the average velocity of the horse.
Solution : We have given
Displacement = 25 km
Time = 4 hr.
Velocity = [tex]\frac{Total\ displacement}{time}[/tex].
Velocity = [tex]\frac{25}{4}[/tex].
Average velocity = 6.25 km/h
Therefore, Average velocity = 6.25 km/h
the sum of one and the product of a number and two is thirteen
Answer:
1+2x=13
Step-by-step explanation:
the sum of= +
one=1
products of a number and 2= 2x
equals= =
thriteen=13
Put them all together:
1+2x=13
Triangle ABC has a perimeter of 12 units. The vertices of the triangle are A(x,2), B(2,-2), and C(-1,2). Find the value of x.
Answer:
The value of x is 2
Step-by-step explanation:
* Lets explain how to find a distance between 2 points
- If the endpoints of a segment are [tex](x_{1},y_{1})[/tex] and
[tex](x_{2},y_{2})[/tex] is [tex]d=\sqrt{(x_{2}-x_{1})^{2}+(y_{2}-y_{1})^{2}}[/tex]
- Triangle ABC has a perimeter of 12 units
∵ The perimeter of any triangle is the sum of lengths of its sides
∴ P Δ ABC = AB + BC + AC
* Lets find the length of the three sides
∵ A = (x , 2) , B = (2 , -2) , C = (-1 , 2)
∵ [tex]AB=\sqrt{(2-x)^{2}+(-2-2)^{2}}[/tex]
∴ [tex]AB=\sqrt{(2-x)^{2}+(-4)^{2}}[/tex]
∴ [tex]AB=\sqrt{(2-x)^{2}+16}[/tex]
∵ [tex]BC=\sqrt{(-1-2)^{2}+(2--2)^{2}}[/tex]
∴ [tex]BC=\sqrt{(-3)^{2}+(4)^{2}}[/tex]
∴ [tex]BC=\sqrt{9+16}[/tex]
∴ [tex]BC=\sqrt{25}[/tex]
∴ BC = 5
∵ [tex]CA=\sqrt{(x--1)^{2}+(2-2)^{2}}[/tex]
∴ [tex]CA=\sqrt{(x+1)^{2}+(0)^{2}}[/tex]
∴ [tex]CA=\sqrt{(x+1)^{2}}[/tex]
- The √ is canceled by power 2
∴ CA = (x + 1)
∵ AB + BC + CA = 12
∴ [tex]\sqrt{(2-x)^{2}+16}[/tex] + 5 + (x + 1) = 12
- Add 5 and 1
∴ [tex]\sqrt{(2-x)^{2}+16}[/tex] + 6 + x = 12
- subtract 6 and x from both sides
∴ [tex]\sqrt{(2-x)^{2}+16}[/tex] = (6 - x)
- To cancel (√ ) square the two sides
∴ (2 - x)² + 16 = (6 - x)²
- Simplify the two sides
∴ [(2)(2) + (2)(2)(-x) + (-x)(-x)] + 16 = (6)(6) + (2)(6)(-x) + (-x)(-x)
∴ 4 - 4x + x² + 16 = 36 - 12x + x²
- Subtract x² from both sides
∴ 20 - 4x = 36 - 12x
- Add 12x to both sides and subtract 20 from both sides
∴ 12x - 4x = 36 - 20
∴ 8x = 16
- Divide both sides by 8
∴ x = 2
* The value of x is 2
At Santa Maria High School the juniors an
are selling raffle tickets. So far, the juniors
solved 580 tickets and are averaging 29 tickets
day. The seniors have sold 490 tickets but vow to
win the contest by selling an average of 35 tickets
per day. If both grades continue collecting at these
rates, after how many days will the number of
tickets sold be equal?
Answer: 580+29x = 490 + 35x
90 = 6x
15 = x
15 days is your answer
Step-by-step explanation:
Suppose that y is directly proportional to x, and y = 6 when x = 54. What is the constant of proportionality?
A) 1/9
B) 1/6
C) 6
D) 9
Answer:
C
Step-by-step explanation:
Answer: The correct option is
(A) [tex]\dfrac{1}{9}.[/tex]
Step-by-step explanation: Given that y is directly proportional to x, and y = 6 when x = 54.
We are to find the constant of proportionality.
According to the given information, we can write that
[tex]y\propto x\\\\\Rightarrow y=kx~~~~~~~~~~~[\textup{where k is the constant of proportionality}]\\\\\Rightarrow k=\dfrac{y}{x}~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]
When y = 6 and x = 54, then from equation (i), we get
[tex]\dfrac{6}{54}=k\\\\\Rightarrow k=\dfrac{1}{9}.[/tex]
Thus, the required value of the constant of proportionality is [tex]\dfrac{1}{9}.[/tex]
Option (A) is CORRECT.